Performance of farmbred Jersey cattle under tropical climatic conditions of Tamil Nadu - A.K. Thiruvenkadan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Data on production and reproduction performances of 373 Jersey cows born and reared at the Exotic Cattle Breeding Farm, Eachenkottai, Tamil Nadu, India, pertaining to 27 years were collected. They were analysed to study the effects of various non-genetic factors on milk production and reproduction traits. The least-squares means (± SE) for 305-day and total lactation milk yields for all the parities were 1491.6 ± 25.9 and 1560.9 ± 29.9 kg respectively. The averages for lactation length, service period, calving interval and dry period for all lactations were 303.1 ± 4.0, 177.0 ± 10.0, 461.0 ± 9.7 and 160.2 ± 9.7 days respectively. Years grouped into five periods had significant (P<0.01) influence on all the traits studied. Season of calving showed a significant (P<0.01) source of variation in milk yield traits and calving interval. Parity was found to influence 305-day milk yield, service period, dry period and calving interval significantly (P<0.01). The study revealed that the performance of the Jersey cattle was much lower than those maintained under high altitude conditions in Tamil Nadu and other places in India.